TerrEduc: revelando o planeta Terra para os pensantes de amanhã - Silva, Iago Bueno da [UNESP]; Ogawa, Fernanda Sueko [UNESP]; Ramalho, Débora Ferrari [UNESP]; Tavares, Marília Manuppella [UNESP]; Lancellotti, Raphaella Patini [UNESP]; Santos, Lucas Albuquerque dos [UNESP]; Lapola, David Montenegro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Climate and environmental changes have brought a major concern regarding the use of natural resources of the Earth, as well as ways to mitigate these impacts. The preparation and awareness of the entire population, mainly in schools, are extremely important to let everyone know how to deal on environmental changes, now and in the future. Interventions in public and private schools were intended to implement the environmental education among the subjects taken by students and assess the knowledge of each student on this new subject. Once students become more familiar with the issue and developed a critical sense about environmental changes, the same are more apt to act on different situations in their routine at the classroom or in the environment where they live.

As mudanças climáticas e alterações no ambiente vêm trazendo consigo uma maior preocupação em relação ao uso dos recursos naturais da Terra, assim como formas de amenizar estes impactos. O preparo e a conscientização de toda a população, principalmente nas escolas, são de extrema importância para que todos saibam lidar com as mudanças no ambiente, agora e no futuro. As intervenções nas escolas pública e privada tiveram como objetivo aplicar a educação ambiental entre as disciplinas cursadas pelos alunos e avaliar o conhecimento de cada turma sobre o assunto. Uma vez que os alunos se familiarizaram mais com o tema e desenvolveram um senso crítico sobre as mudanças ambientais, os mesmo estão mais aptos a agir diante de diferentes situações em seu cotidiano, seja em sala de aula ou no ambiente onde vivem.
Keywords: Environmental education; Awareness; Natural resources; Educação ambiental; Conscientização; Recursos naturais